Fiscal Vulnerability and Sustainability in Oil-Producing Sub-Saharan African Countries - Zhan, Zaijin; York, Robert (Washington, D.C. : International Monetary Fund, 2009)
Over many years rises and fall of world oil prices have been repeatedly reflected in the boom-bust cycles in oil-exporting countries the world over. The recent spectacular rise and equally spectacular fall in prices provides an opportunity to inquire whether anything is different this time. In this paper we limit the analysis to the experience, outlook, and longterm fiscal policy considerations for eight of the world's oil-producing countries in sub- Saharan Africa. Because we are interested in gauging their fiscal vulnerability and sustainability from the angle of managing exhaustible oil wealth, we focus on the non-oil primary balance as the relevant indicator of how initial conditions and resource endowments can influence long-term considerations in several different models of fiscal rules.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet